Performance Appraisal System At Mitra Uniform Batam - Cherlyn Cherlyn; Antony Sentoso (ConCEPt - Conference on Community Engagement Project, 2023)
Mitra Uniform Batam is a business that engaged in the production of various types of clothing for business as shirt for promotion product, businesses, communities, event, exhibitions, seminar and others. In running this business the owner stated that there was a problem about there is the evaluation method for employee performance appraisal is wrong. Performance appraisal is a civil servants plays a very important role, such as to see how civil servants perform, but also to see how the development of skill and competencies and career path of civil servants progresses. Previously the performance appraisal was only was estimated by the manager himself. The method of the research is using primary data from observation and interview also secondary data from journals. After implementing the activities carried out, the frequency of turnover is reduced. This causes partners to minimize their losses